Functional brain connectivity of remembered fatigue or happiness in healthy adults: Use of arterial spin labeling. Issue 3 (16th March 2018) - Boissoneault, Jeff; Sevel, Landrew; Robinson, Michael E.; Staud, Roland
ABSTRACT: Introduction : Chronic fatiguing illnesses like cancer, multiple sclerosis, chronic fatigue syndrome, or depression are frequently associated with comorbidities including depression, pain, and insomnia, making the study of their neural correlates challenging. To study fatigue without such comorbidities, functional connectivity (FC) analyses were used in healthy individuals to study brain activity during recall of a fatiguing event inside the MRI scanner. A positive mood induction served as control condition. Method : Using SPM8 and the CONN toolbox, FC was tested using seed- and independent component- based (ICA) analyses. Differences in the FC correlations between seed-to-voxel and ICA clusters between conditions were assessed with permutation testing. Results : 17 participants (59% women) achieved mean ( SD ) in-scanner fatigue VAS ratings of 31.85 (20.61). Positive mood induction resulted in happiness ratings of 46.07 (18.99) VAS. Brain regions where alterations in FC correlated with fatigue included the globus pallidum, left lateral occipital cortex, and cuneus. FC of happiness involved the parahippocampal gyrus, both supplemental motor areas, as well as right superior frontal gyrus. Using data-driven ICA, we identified an intra-cerebellar network where several regions were significantly associated with fatigue, but not happiness ratings. Results of permutation testing provided evidence that the detected clusters correlated differentially with self-reported fatigue and happiness. Conclusions : Our study suggests that functional interactions between globus pallidum and occipital structures contribute to experimental fatigue in healthy individuals. They also highlight the important role of cortico-cerebellar interactions in producing feelings of fatigue. FC of occipital structures contributed to both experimental fatigue and happiness ratings.